PubMed Central: An Essential Resource for Information Professionals and Researchers - Jordan, Joanne L. (Evidence Based Library and Information Practice, 2013)
Objective – A review of the journals containing research listed in PubMed Central (PMC), but not selected for inclusion in the National Library of Medicine (NLM) collection. The authors identified reasons why journals had not been included in the collection and if any met the NLM selection criteria and were appropriate for inclusion. Design – Descriptive study. Setting – National Library of Medicine, United States. Subjects – 571 journals that were not included in the NLM collection but had research articles in PMC. Methods – In October 2009, a report was produced from the NLM library system listing journals tagged as having articles in PMC and not being in the NLM collection. Information was gathered on the journals identified and these were checked against the Collection Development Manual of the NLM and the NLM checklist used for selecting electronic journals. The reason for non-selection of the journal was recorded and the subject category, according to the Library of Congress Classification, was noted. Recorded reasons why journals were not selected: • Less than 15% of articles were within scope of NLM collection • Not enough articles published • Coverage (lacking original research or not for a scholarly audience) • Insufficient information to determine reason For journals where the criteria seemed to be met, the decision on selection to the NLM collection was reviewed. Main Results – The authors identified 571 journals that had articles in PMC but did not meet the criteria for inclusion in the NLM journal collection. The majority of these journals (73%) were outside the NLM scope and a further 10% had not published a sufficient number of articles to be considered. A further 3% were assessed as not intended for a scholarly audience or lacked original research and another 3% could not be reviewed due to lack of information available. There were 65 journals (11%) that were referred for further review as the selection criteria seemed to be met and 11 of these journals have subsequently been added to the NLM collection. This is in relation to 482 new print and electronic journals in total that were added to the NLM collection in 2009. However, only 369 of the 571 journals (65%) had one or more articles included in PMC; of these, 238 had one article and 33 had more than four articles in the archive. The reason that some journals had no articles in PMC at the time of this review was due to the time it takes to process new articles and embargos set by the publishers that restrict immediate listing on open access databases such as PMC. A number of these journals may also be new and may not have had a sufficient number of articles or enough information available to be able to include them in the NLM collection. To add context, the authors state that PMC contained over 115,000 NIH-funded articles by the end of November 2010. The subject areas these non-selected journals were classified under included Engineering (15%); Medicine (14%); Mathematics (10%); Chemistry (10%); and Computer Science (9%). Library Science was assigned to 2% of the journals. The Medicine journals were more likely than those in the other subject areas to be new journals without sufficient articles to be included in the NLM collection. Conclusion – When the journal title is out of the scope of the NLM collection, an individual article in that journal can still be included in PMC. This provides a solution to the problem of how to collect biomedical research that is not published in biomedical journals. This may be more important in the future as the field becomes more interdisciplinary. This also provides a useful resource for libraries and researchers searching for full-text biomedical articles. The authors conclude that analyzing the articles from the journals not selected for inclusion in the NLM collection will provide helpful information about the types of biomedical research being published in non-biomedical journals. This will highlight particular areas the NLM should pay attention to in the future.